Accumulation of rare earth element (rees) in pistia stratiotes (water lettuce) and oreochromis niloticus (nile tilapia) in rees artificial industrial wastewater system - Omar, Muhammad Nor; Mohd Aris, Mohd Shukri; Abu Samah, Mohd Armi; Yunus, Kamaruzzaman; Nazreen, Muhd N. Muhammad (2019)
The manufacturing of rare earth element (REE) especially lanthanum (La) is susceptible in causing environmental contamination by discharging its industrial wastewater into the environment especially ponds, lakes and rivers. The REE wastewater containing La residue and other radioactive elements will be uptaken by the aquatic plants and freshwater fish through bioaccumulation process. Therefore, this study aims to determine the effectiveness of the aquatic plant (Pistia stratiotes) and freshwater fish (Oreochromis niloticus) as bioaccumulation agents of La in REE artificial wastewater system. The study was carried out by subjecting P. stratiotes (water lettuce) and O. niloticus (Nile tilapia) to 4 levels of lanthanum chloride (LaCl3) solutions (i.e. 1, 3, 5 and 10 ppm) for 12 days in aquaponics artificial wastewater system. The samples were collected every two days and dried prior to digestion. The dried plant parts (root and leaf) and fish tissues (stomach and flesh) were acid-digested and then analyzed the REE metal (La) accumulation using the Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The results showed that lanthanum (La) were accumulated in both the root and leaf sections of P. stratiotes and in the stomach and flesh of O. niloticus. In P. stratiotes; the highest concentration of lanthanum was found in the root section (0.083 ppb) of the plant collected on the 6th day from the aquaponic tank containing 10 ppm LaCl3 compared to the leaf section (0.061 ppb) collected on the 12th day from the tank containing 3 ppm LaCl3.. However, in O. niloticus, the highest concentration of lanthanum was found in the stomach tissue (8.41 ppb) of the fish collected on the 6th day from the aquaponic tank containing 1 ppm LaCl3 compared to the flesh section (0.107 ppb) collected on the 8th day from the aquaponic tank containing 5 ppm LaCl3. The accumulated La trends between fish tissues (O. niloticus) and plant parts (P. stratiotes) were also different. The fish (O. niloticus) grown in the tank containing 1 ppm of La solution, the accumulated La in its stomach showed an increasing trend between 2nd and 6th day of exposure and then decreased afterward. Meanwhile, in the flesh, it showed a similar trend as observed in the stomach. However, the accumulated La in roots of P. stratiotes indicated the trends were fluctuated throughout all days of exposures. When the plants exposed in 1 ppm of La solution, the accumulations of La in their roots were maximum at 6th and 12th day of exposure respectively. Finally, in the leaves of P. stratiotes, all trends were in increasing trends throughout the duration of exposures. The study concludes that the aquatic plant (P. stratiotes) and the freshwater fish (O. niloticus) can accumulate the REE element (La); thus may be used as a phytoremediator and bioindicator for monitoring the REE contamination because of their bioaccumulation capabilities.